Lymphocyte‐to‐monocyte ratio: a novel marker for critical limb ischemia in PAOD patients. Issue 12 (31st October 2014) - Gary, T.; Pichler, M.; Belaj, K.; Eller, P.; Hafner, F.; Gerger, A.; Brodmann, M.
Summary: Background: The lymphocyte‐to‐monocyte ratio (LMR) is easily determined from the white blood cell count. Lymphocytes were previously investigated as a part of the neutrophil‐to‐lymphocyte ratio (NLR) in patients with atherosclerotic disease and an elevated NLR was negatively associated with cardiovascular endpoints. As monocytes play a leading role in the progression of atherosclerosis, especially in peripheral arterial occlusive disease (PAOD), we investigated LMR and its association with critical limb ischemia and other vascular endpoints in PAOD patients. Methods and Findings: We evaluated 2121 PAOD patients treated at our institution from 2005 to 2010. LMR was calculated and the cohort was divided into tertiles according to the LMR. An optimal cut‐off value for the continuous LMR was calculated by applying a receiver operating curve analysis to discriminate between CLI and non‐CLI. In our cohort occurrence of CLI decreased significantly with an increase in LMR. An LMR of 3.1 was identified as an optimal cut‐off. Two groups were categorized, one with 1021 patients (LMR < 3.1) and a second one with 1100 patients (LMR ≥ 3.1). CLI was more frequent in LMR < 3.1 patients [426 (41.7%)] than in LMR ≥ 3.1 patients [254 (23.1%)] (p < 0.001), as was also the case with prior myocardial infarction [60 (9.5%) vs. 35 (3.2%), p = 0.003] and congestive heart failure [136 (13.3%) vs. 66 (6.0%), p < 0.001). As to inflammatory parameters, C‐reactive protein [median 9.0 mg/l (4.0–30.0) vs. median 4.0 mg/l (2.0–8.0)] and fibrinogen (median 438 mg/dl (350–563) vs. 372 mg/dl (316–459.5)] also differed significantly in the two patient groups (both p < 0.001). A LMR < 3.1 was associated with an odds ratio (OR) of 2.0 (95% CI 1.8–2.2, p < 0.001) for CLI, even after adjustment for other vascular risk factors. Conclusions: A decreased LMR is significantly associated with a high risk for CLI and other vascular endpoints. The LMR is an easily determinable, broadly available and inexpensive marker that could be used to identify patients at high risk for vascular endpoints.